(untitled) (Scientific journal of the Fergana State University, 2025)
The art of personification is one of the earliest and most ancient tools of fiction. However, in medieval Persian-Tajik poetics, it was largely overlooked by scholars, and existing treatises examined only certain features of this art rather than all its aspects. In classical Persian-Tajik poetics, also referred to as the science of literature, scholars did not document this literary art form for many years. Although examples of personification were widely employed in ancient mythology, folk oral literature, written sources, the literature of the Iranian peoples, and classical Persian-Tajik poetry, medieval poetics did not recognize it as a distinct type of poetic art. Instead, the art of personification was studied within the framework of metaphor and simile, rather than as an independent poetic art. In terms of its theoretical characteristics and significant content, personification fundamentally differs from metaphor and simile. In many cases, its form and structure do not conform to the framework of metaphor and simile, and it stands out primarily as a distinct poetic art. This article examines the theoretical features of personification, its independence from metaphor and simile, and the perspectives of Persian-Tajik poetry scholars on this subject.